Joseph and the amazing technicolor dreamcoat [videorecording (DVD)] - Lloyd Webber, Andrew, 1948- (Universal Studios, 2000)
In this filmed adaption of the long-running humourously musical interpretation of the Biblical story of Joseph, favored son of Jacob of Canaan, and his coat of many colors, Joseph is betrayed by his jealous brothers, sold into slavery, and driven to Egypt where he is beset with adversity but perseveres through wit and faith to become the governor of Egypt, second only to the Pharaoh.